Electronic structure and magnetism of epitaxial Ni–Mn–Ga(-Co) thin films with partial disorder: a view across the phase transition. (27th October 2017) - Schleicher, B; Klar, D; Ollefs, K; Diestel, A; Walecki, D; Weschke, E; Schultz, L; Nielsch, K; Fähler, S; Wende, H; Gruner, M E
Abstract: The influence of Co-doping in off-stoichiometric Ni–Mn–Ga and Ni–Mn–Ga–Co thin films on the magnetic coupling of the atoms is investigated with x-ray magnetic circular dichroism in both the martensitic as well as austenitic phase, respectively. Additionally, first principles calculations were performed to compare the experimentally obtained absorption spectra with theoretical predictions. Calculated exchange constants and density of states for the different atomic sites underline the large influence of chemical and magnetic order on the magnetocaloric properties of the material.